Lessons in aging from Myc knockout mouse models - Prochownik, Edward V.; Wang, Huabo (Frontiers in Cell and Developmental Biology, 2023)
Despite MYC being among the most intensively studied oncogenes, its role in normal development has not been determined as Myc-/-mice do not survival beyond mid-gestation. Myc+/-mice live longer than their wild-type counterparts and accumulate many age-related phenotypes more slowly. However, Myc haplo-insufficiency likely conceals other important phenotypes as many high-affinity Myc targets genes continue to be regulated normally. A recent report has described the generation of mice with body-wide and, in most tissues, near complete Myc "knockout" by delaying its inactivation until after birth. Unexpectedly, these mice also lived significantly longer than control wild-type mice but manifested a marked premature aging phenotype. This seemingly paradoxical behavior was potentially explained by a >three-fold lower lifetime incidence of cancer, normally the most common cause of death in mice. Myc loss accelerated the onset of numerous "Aging Hallmarks", including the loss of mitochondrial and ribosomal structural and functional integrity, the generation of reactive oxygen species, genotoxic damage, detrimental metabolic rewiring and the onset of senescence. In both mice and humans, normal aging in many tissues was associated with the down-regulation of Myc and the loss of Myc target gene regulation. Unlike most mouse models of premature aging, which are based on defects in DNA damage recognition and repair, the MycKO mouse model directly impacts most Aging Hallmarks and may therefore more faithfully replicate the normal aging process of both mice and humans. It also establishes that the strong association between aging and cancer is transcriptionally maintained by a single gene.